DEVELOPING OF STUDENT WORKSHEETS BASED ON INQUIRY IN TEMPERATURE AND HEAT MATERIAL IN CLASS XI ACADEMIC YEAR 2020/2021 - Tiovani Ariesta Pasaribu; Muhammad Kadri (INPAFI (Inovasi Pembelajaran Fisika), 2021)
This study aims to develop inquiry learning-based physics worksheets on the material of temperature and heat. The subjects in this study were students of 11 grade sciences Nasrani Private School 3 Medan totaling 20 students. The research method is Research and Development (R&D) using 4D (Define, Design, Develop and Disseminate) development model by S.Thiagarajan and Semmel (1994). The instruments used consisted of a material expert validation questionnaire, learning experts, a teacher assessment questionnaire in the field of study, and a student response questionnaire. The data analysis technique used is descriptive. The results of data analysis obtained validation of material experts by 85%, learning experts by 65%, teacher assessments by 87%. The response of students in a limited trial with a sample of 5 people was 74% included in the good criteria. Meanwhile, in the wide trial, the percentage of student responses with a sample of 20 people was 91.5% with very good criteria for learning process.